Towards Fusion: New Trends in Hindustani Sitar Music in Malaysia - Pravina Manoharan, (Wacana Seni Journal of Arts Discourse, 2008)
While a classical Sitar recital in Malaysia still retains many of its original forms and practices, local sitarists are experimenting with new musical ideas to promote the Sitar and its music to a wider audience of mixed ethnicity. Musicians combine Hindustani musical elements such as Raag (melody) and Taal (rhythmic cycle) with different musical elements such as the Chinese pentatonic scale and Arabian Maqam as well as new genres to produce a musical blend broadly dubbed as ‘fusion music’. This article explores how the characteristics of the Hindustani elements of Raag and Taal are adopted to complement the structure and style of the new compositions. Different Sitar playing styles and techniques are employed in the performance of fusion compositions that use Blues or Bossa Nova genres.